Analisis Tindak Tutur Direktif dan Ekspresif dalam Teks Ceramah pada Buku Bahasa Indonesia Kelas 11 SMA Kurikulum 2013 - Lailia Fahrunnisa Hidayati; Arfiatun Astia Ningrum; Gita Ratri Utami; Zahidah Haibah; Desi Fatmasari; Wahyu Ningrum; Asep Purwo Yudi Utomo (STIKes Ibnu Sina Ajibarang, 2024)
Pragmatics is a language study that examines the speaker's intentions. If someone speaks positive speech, the speaker can also have a positive impact on what the speaker conveys, and vice versa. Speech acts have many types, one of which is directive and expressive speech acts. Directive speech acts are speech acts that can cause the speaker to carry out commands or directions from the speaker. These speech acts are also called impositive speech acts. Expressive speech acts are speech acts that express an action or psychological statement from the speaker, which can be in the form of joy, likes or dislikes, and sadness. The aim of this research is to describe directive speech acts and expressive speech acts, to know the functional categories of directive speech acts and expressive speech acts, to make it easier to understand the expressed and implied meaning, to know the difference between directive speech acts and expressive speech acts in book lecture texts. Indonesian language class In the Lecture Texts in the 2013 High School Class 11 Indonesian Language Teaching Material Book, the 2013 Curriculum is dominated by the type of directive speech acts (TTD), totaling 17 speech acts, and expressive speech acts (TTE), totaling 16 speech acts. This research is useful as learning material in the scientific field and also as a forum so that students can easily grasp and understand the meaning and meaning conveyed in a writing by the author and are able to hone their skills in analyzing directive speech acts and expressive speech acts.